Carbohydrate mouthwashes and their effect on running time trial performance: Systematic review - Fuentes-Barría, Héctor; Aguilera-Eguía, Raúl; González-Wong, Catalina; Flores-Fernández, Cherie; Herrera-Serna, Brenda; Valenzuela-Pérez, Diego; Urbano-Cerda, Sebastián (Universidad y Salud, 2020)
Introduction: Currently, the effects of carbohydrate mouthwash use on sports performance are controversial. While some studies have shown ergogenic effects, others have not demonstrated any advantage. Objective: To determine whether there is scientific evidence to support the different protocols for carbohydrate mouthwashes use and their effect on sports performance in cycling races time trial. Materials and methods: A search of literature published between 2015 and 2019 was conducted in the Medline, Cochrane Library, and Scopus databases using the terms "Carbohydrates", "Mouth rinses" and "Athletic performance". Results: 7 out of 96 reviewed studies were selected, which included different population groups, evaluation methods, and doses of rinsing carbohydrates. The results obtained on the impact of carbohydrate mouthwashes on sport performance were controversial as only some studies demonstrated an ergogenic effect. Conclusions: As the effects of carbohydrate mouthwashes are debatable, it cannot be assured that they improve performance in different cycling races time-trial. More randomized controlled studies are required to homogenize and identify the specific action mechanisms through which carbohydrate mouthwashes act on different study populations.